DEVELOPMENT OF INFORMATION COMPETENCIES IN THE FILD OF RADIATION TECHNOLOGIES THROUGH CURRICULAR ACTIVITIES - Baimuratova, Irina (SCIENCE and SOCIETY, 2026)
This article discusses the integration of innovative methods in teaching radiation technology at higher medical institutions, which leads to increased learning efficiency and the formation of key student competencies. It demonstrates the integration of information technologies in radiation technology, from computers to accelerators, which requires the development of a curriculum at the intersection of these fields. It emphasizes the need for the interaction of three basic competencies: intellectual, personal, emotional, and social skills, which are best developed through innovative teaching methods.